KEGAGALAN PARTAI POLITIK MENARIK SIMPATI RAKYAT: Urgensi Sebuah Paradigma Baru Partai Politik - Noor, Firman (Pusat Penelitian Politik, 2007)
This paper encourages political parry to take into account a new paradigm in conducting their activities in Indonesia today. By emphasizing the importance ofcareness and the commitment ofserving people, as the essence ofthe new paradigm for political parties, this paper believe that this paradigm is actually in line with the spirit of the national political history and a contemporary understanding of politics. This paper considers that this paradigm is important to enhance the relation between people and the political party also, to regain the trust of the people, which in the end will preserve the existence ofdemocracy in Indonesia.